2016
DOI: 10.1111/wej.12216
|View full text |Cite
|
Sign up to set email alerts
|

Exploring bioaugmentation strategies for azo dye CI Reactive Violet 5 decolourization using bacterial mixture: dye response surface methodology

Abstract: The use of response surface methodology based on statistical design of experiments is becoming increasingly widespread in several sciences such as analytical and environmental chemistry. In the present study, the decolourization and the degradation efficiency of CI Reactive Violet 5 (CIRV5) was studied using a novel bacterial consortium. CIRV5 (1000 p.p.m.) biodegradation was investigated under shaking condition in mineral salt medium solution (MSM) at a 7.5 pH and a 25°C temperature. The degradation pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Finally, Ayed et al [31] explored the feasibility of using a consortium of Staphylococcus species, two of which were isolated from a textile wastewater, to degrade RV5. Under optimal conditions, the dye solution was completely (>99%) decolorized within 8 h. The decolorization was also accompanied by a high COD (Chemical Oxygen Demand) removal (94.93%) Therefore, the results obtained in the present study indicate that the degradation of RV5 by a Fe-doped titania catalyst under visible light irradiation can lead to dye removal efficiencies that are comparable with those reported for UV-photocatalytic or microbial treatments.…”
Section: Comparison With the Results Of Other Published Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Ayed et al [31] explored the feasibility of using a consortium of Staphylococcus species, two of which were isolated from a textile wastewater, to degrade RV5. Under optimal conditions, the dye solution was completely (>99%) decolorized within 8 h. The decolorization was also accompanied by a high COD (Chemical Oxygen Demand) removal (94.93%) Therefore, the results obtained in the present study indicate that the degradation of RV5 by a Fe-doped titania catalyst under visible light irradiation can lead to dye removal efficiencies that are comparable with those reported for UV-photocatalytic or microbial treatments.…”
Section: Comparison With the Results Of Other Published Studiesmentioning
confidence: 99%
“…However, its complex aromatic structure ( Figure 1) makes it highly resistant to degradation. A literature survey showed that very few studies have been performed on RV5 degradation and none of them investigated the photocatalytic removal of the dye under visible light [27][28][29][30][31][32]. Accordingly, a first aim of this study was to evaluate whether the use of the selected photocatalyst in the presence of visible light could be a suitable method to degrade RV5.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the correlation coefficient (R 2 = 0.999) with a predicted correlation coefficient (Pred R 2 = 0.996) and adjusted correlation coefficient (adj R 2 =0.998) signifies that this model might be used to predict response quite efficiently for a given process condition or vice versa. The higher R 2 value reveals a better representation of experimental data by the developed quadratic regression model . The adequate precision value of 97.72 indicates a sufficient signal to noise ratio.…”
Section: Resultsmentioning
confidence: 95%
“…The confidence interval around this lambda includes current point value of 1, which matches the model design value. Hence, further transformation is not necessary for the observed response during model fitting . Figure d shows leverage versus run the plot of the quadratic model, which ensures that all numerical values are obtained within the standard limits range of 0–1 of an experimental trial.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic dyes are used in many fields, such as textile, plastic, cosmetic, and tannery industries: approximately 800.000 tons of dyes are produced every year all over the world, their global demand being predicted yet to grow in the next years [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%